Individual and country‐level variables associated with the medicalization of birth: Multilevel analyses of IMAgiNE EURO data from 15 countries in the WHO European region - Miani, Céline (2022)
Objective: To investigate potential associations between individual and country- level factors and medicalization of birth in 15 European countries during the COVID- 19 pandemic. Methods: Online anonymous survey of women who gave birth in 2020– 2021. Multivariable multilevel logistic regression models estimating associations between indicators of medicalization (cesarean, instrumental vaginal birth [IVB], episiotomy, fundal pressure) and proxy variables related to care culture and contextual factors at the individual and country level. Results: Among 27 173 women, 24.4% (n = 6650) had a cesarean and 8.8% (n = 2380) an IVB. Among women with IVB, 41.9% (n = 998) reported receiving fundal pressure. Among women with spontaneous vaginal births, 22.3% (n = 4048) had an episiotomy. Less respectful care, as perceived by the women, was associated with higher levels of medicalization. For example, women who reported having a cesarean, IVB, or episiotomy reported not feeling treated with dignity more frequently than women who did not have those interventions (odds ratio [OR] 1.37; OR 1.61; OR 1.51, respectively; all: P < 0.001). Country- level variables contributed to explaining some of the variance between countries. Conclusion: We recommend a greater emphasis in health policies on promotion of respectful and patient- centered care approaches to birth to enhance women's experiences of care, and the development of a European- level indicator to monitor medicalization of reproductive care.